Picard group of moduli of parabolic Higgs bundles. Issue 2 (1st February 2023) - Roy, Sumit
Abstract: Let X be a compact Riemann surface of genus g ≥ 3 and let M par be the moduli space of semistable parabolic bundles over X . Let M parH denote the moduli space of semistable parabolic Higgs bundles over X . In this article, we study the Picard group of M par and M parH .